(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze several factors associated with the severity of pneumococcal pneumonia in children aged from 2 months to under 5 years at the Pediatric Center, Thai Nguyen Central Hospital during 2024–2025. Methods: A cross-sectional descriptive study was conducted on 153 children aged from 2 months to under 5 years who were diagnosed with community-acquired pneumococcal pneumonia at the Pediatric Center, Thai Nguyen National Hospital. Results: mean age of the children was 22.80 ± 14.88 months. Severe pneumonia accounted for 42.5% of cases. Children with a birth weight below 2,500 grams had a significantly higher rate of severe pneumonia compared with those whose birth weight was 2,500 grams or higher (72.2% vs. 38.5; p<0.05). In addition, children with incomplete immunization history had a higher proportion of severe pneumonia than those who were fully immunized (47.9% vs. 21.9; p<0.05). Severe pneumococcal pneumonia in children aged from 2 months to under 5 years is influenced by early-life risk factors and preventive capacity. Strengthening antenatal care, improving birth nutritional status, and ensuring complete immunization play a crucial role in reducing disease severity and the overall burden of childhood illness.